2012
DOI: 10.1111/j.1365-2966.2012.21076.x
|View full text |Cite
|
Sign up to set email alerts
|

Dead zones around young stellar objects: FU Orionis outbursts and transition discs

Abstract: We perform global time‐dependent simulations of an accretion disc around a young stellar object with a dead zone (a region where the magneto‐rotational instability cannot drive turbulence because the material is not sufficiently ionized). For infall accretion rates on to the disc of around 10−7 M⊙ yr−1, dead zones occur if the critical magnetic Reynolds number is larger than about 104. We model the collapse of a molecular gas cloud. At early times when the infall accretion rate is high, the disc is thermally i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…Hartmann (1998) argues that disc accretion is inherently intermittent and that the main difference between FUor and EXor outbursts is the evolutionary stage in which they take place, with FU Ori outburst occurring preferentially during the embedded stage and EXor outbursts occurring during the T Tauri phase. At least four outburst mechanisms have been proposed to date: 1) the coupling of magnetorotational and gravitational instabilities (MRI+GI, Armitage et al 2001, Zhu et al 2009, Martin et al 2012, 2) disc fragmentations followed by the inward migration of the resulting fragments (Vorobyov & Basu 2005, Zhu et al 2012), 3) Thermal-viscous instability (Bell et al 1995), and 4) instabilities induced by planets (Clarke et al 1990, Lodato & Clarke 2004 or stellar companions (Bonnell & Bastien 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Hartmann (1998) argues that disc accretion is inherently intermittent and that the main difference between FUor and EXor outbursts is the evolutionary stage in which they take place, with FU Ori outburst occurring preferentially during the embedded stage and EXor outbursts occurring during the T Tauri phase. At least four outburst mechanisms have been proposed to date: 1) the coupling of magnetorotational and gravitational instabilities (MRI+GI, Armitage et al 2001, Zhu et al 2009, Martin et al 2012, 2) disc fragmentations followed by the inward migration of the resulting fragments (Vorobyov & Basu 2005, Zhu et al 2012), 3) Thermal-viscous instability (Bell et al 1995), and 4) instabilities induced by planets (Clarke et al 1990, Lodato & Clarke 2004 or stellar companions (Bonnell & Bastien 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Fleming 2000), and the viscosity parameter α. Martin et al (2012a) showed that in order to reproduce FU Orionis outbursts, ReM,crit must be a few 10…”
Section: Discussionmentioning
confidence: 99%
“…We use a one dimensional layered disc model described in Martin & Lubow (2011) and further developed in Martin et al (2012a) to evolve the total surface density, Σ(R, t) and mid-plane temperature, Tc(R, t). We take a solar mass star, M = 1 M⊙, with a disc that extends from a radius of R = 5 R⊙ up to R = 40 AU.…”
Section: Protoplanetary Disc Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The dead zone surface density is determined via a critical magnetic Reynolds number (e.g., Hawley et al 1995;Fleming et al 2000;Martin et al 2012aMartin et al , 2012b (Blaes & Balbus 1994) and x e is the electron fraction. We use the analytic approximations for the active layer surface density shown in Equations (27) and (28) in Martin et al (2012a) that include thermal ionization, cosmic ray ionization, and the effects of recombination.…”
Section: Disk Model With a Dead Zonementioning
confidence: 99%